2008
DOI: 10.1128/aem.01249-08
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Salmonella enterica Serovar Heidelberg Isolates from Retail Meats, Including Poultry, from 2002 to 2006

Abstract: Salmonella enterica serovar Heidelberg frequently causes food-borne illness in humans. There are few data on the prevalence, antimicrobial susceptibility, and genetic diversity of Salmonella serovar Heidelberg isolates in retail meats. We compared the prevalences of Salmonella serovar Heidelberg in a sampling of 20,295 meats, including chicken breast (n ‫؍‬ 5,075), ground turkey (n ‫؍‬ 5,044), ground beef (n ‫؍‬ 5,100), and pork chops (n ‫؍‬ 5,076), collected during 2002 to 2006. Isolates were analyzed for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 20 publications
11
107
1
8
Order By: Relevance
“…In this study, Salmonella serotypes, Derby, Hato, Hermannswerder, Urbana, Shangani, Tamberma, Kentucky, Muenster, Senftenberg, Shangani, Typhi and Typhimurium were MDR. This is similar to the findings of many authors, who reported that MDR Salmonella strains have been found to be of many serotypes such as Agona, Anatum, Pullorum, Schwarzengrund, Choleraesuis, Derby, Dublin, Heidelberg, Kentucky, Newport, Senftenberg, Typhimurium, and Uganda (Chen et al, 2004;Zhao et al, 2008). All S. Typhimurium reported in the present study were MDR and most of them were found to display a phenotype of resistance to ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline (ACSSuT).…”
Section: Resultssupporting
confidence: 80%
“…In this study, Salmonella serotypes, Derby, Hato, Hermannswerder, Urbana, Shangani, Tamberma, Kentucky, Muenster, Senftenberg, Shangani, Typhi and Typhimurium were MDR. This is similar to the findings of many authors, who reported that MDR Salmonella strains have been found to be of many serotypes such as Agona, Anatum, Pullorum, Schwarzengrund, Choleraesuis, Derby, Dublin, Heidelberg, Kentucky, Newport, Senftenberg, Typhimurium, and Uganda (Chen et al, 2004;Zhao et al, 2008). All S. Typhimurium reported in the present study were MDR and most of them were found to display a phenotype of resistance to ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline (ACSSuT).…”
Section: Resultssupporting
confidence: 80%
“…Salmonella serovar Heidelberg are resistant to ceftiofur, streptomycin, tetracycline, sulfamethoxazole, chloramphenicol and trimethoprim-sulfamethoxazole. This strain of Salmonella derived from poultry products is specifically important due to its ability to cause extra intestinal infection like septicemia [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella species are considered to be among the most important foodborne pathogens in the world and salmonellosis is still one of the most widespread foodborne bacterial illnesses in humans, with clinical manifestations ranging from asymptomatic state to severe disease [2]. The majority of infections are associated with the ingestion of contaminated foods such as poultry, beef, pork, eggs, milk, cheese, seafood, fruits, juices, and vegetables [3,4], although most infections caused by multidrugresistant Salmonella are acquired through contaminated foods of animal origin.…”
Section: Introductionmentioning
confidence: 99%